PRAMUSAJI DI KAWASAN WISATA KULINER WAKEKE KOTA MANADO - Liwan, Christine C. (Universitas Sam Ratulangi, 2015)
Tourism as an industry is the existence of very complex and very sensitive to the various changes and development. The changes mainly related to desire or motivation of the tourists who always want to find and enjoy something new to the gratification of desire or his personal experience, something different from ever perceived before. Local cultural variety which can be used as assets that cannot be likened to local culture other countries. Local cultural specificity of this often interesting views other countries.Kota Manado as a tourism destination culinary especially already exist since launching of culinary tourism area Wakeke since 2004 by the local governments. The development of tourism not only the government only in presenting the potential of nature and culture.The participation of all components in terms of business, developers and services not separated from the vision and mission to attract tourists interested in visiting into a tourist destination. Business in the service sector such as travel, hotel, restaurant, souvenirs, guidance, transportation and others trying to provide the most of service.Waitress for example is one of the elements that seem to be giving the meaning of in the development of tourism but they become the spearhead in offer a service that friendly, polite and appreciate so the tourists visitors satisfied and want to visit back. Keywords: waitress, tourism, service